Restricted diffusion of a freely diffusible second messenger: mechanisms underlying compartmentalized cAMP signalling. (21st July 2006) - Zaccolo, M.; Di Benedetto, G.; Lissandron, V.; Mancuso, L.; Terrin, A.; Zamparo, I.
Abstract : It is becoming increasingly evident that the freely diffusible second messenger cAMP can transduce specific responses by localized signalling. The machinery that underpins compartmentalized cAMP signalling is only now becoming appreciated. Adenylate cyclases, the enzymes that synthesize cAMP, are localized at discrete parts of the plasma membrane, and phosphodiesterases, the enzymes that degrade cAMP, can be targeted to selected subcellular compartments. A-kinase-anchoring proteins then serve to anchor PKA (protein kinase A) close to specific targets, resulting in selective activation. The specific activation of such individual subsets of PKA requires that cAMP is made available in discrete compartments. In this presentation, the molecular and structural mechanisms responsible for compartmentalized PKA signalling and restricted diffusion of cAMP will be discussed.